2013
DOI: 10.1371/journal.pone.0071081
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Prion Protein Refolded with Lipid and RNA Has the Biochemical Hallmarks of a Prion but Lacks In Vivo Infectivity

Abstract: During prion infection, the normal, protease-sensitive conformation of prion protein (PrPC) is converted via seeded polymerization to an abnormal, infectious conformation with greatly increased protease-resistance (PrPSc). In vitro, protein misfolding cyclic amplification (PMCA) uses PrPSc in prion-infected brain homogenates as an initiating seed to convert PrPC and trigger the self-propagation of PrPSc over many cycles of amplification. While PMCA reactions produce high levels of protease-resistant PrP, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 70 publications
4
45
0
Order By: Relevance
“…More recently, wild-type mice developed clinical disease typical of TSE at about 130 days after injection of proteinase K (PK)-resistant rPrP fibrils generated by unseeded PMCA in the presence of 1-palmitoyl-2-oleoylphosphatidylglycerol (POPG), a synthetic lipid molecule, and total liver RNA (22). Although these results were reproduced by the same group (23), others have reported that rPrP fibrils generated by the same method were unable to induce either neuropathological changes or the accumulation of PrP Sc (24). Thus, the role of POPG and RNA in the de novo generation of infectious rPrP fibrils remains controversial.…”
mentioning
confidence: 94%
“…More recently, wild-type mice developed clinical disease typical of TSE at about 130 days after injection of proteinase K (PK)-resistant rPrP fibrils generated by unseeded PMCA in the presence of 1-palmitoyl-2-oleoylphosphatidylglycerol (POPG), a synthetic lipid molecule, and total liver RNA (22). Although these results were reproduced by the same group (23), others have reported that rPrP fibrils generated by the same method were unable to induce either neuropathological changes or the accumulation of PrP Sc (24). Thus, the role of POPG and RNA in the de novo generation of infectious rPrP fibrils remains controversial.…”
mentioning
confidence: 94%
“…In addition, the interaction between recombinant PrP C and nucleic acids (DNAs, tRNA, and PolyA) simultaneously produces a mixture of condensed and functionally active nucleoprotein complex, PrP Sc oligomers and linear and spherical amyloids. [8][9][10][11][12] A specific nucleic acid as a cofactor for the propagation of prion infection has not been identified. 13 PrP C is a cell surface protein and nucleic acids in extracellular circulation can interact with it.…”
Section: Introductionmentioning
confidence: 99%
“…16 The presence of prion protein in cytoplasm of cells including neurons has been shown and although the exact biological role of prion proteinnucleic acid interaction is not known at present, it is possible that structural conversion of PrP C to PrP Sc can be catalyzed by cytoplasmic nucleic acids that can play a role in the prion diseases. 12,17,18 A separate study indicates the neurotoxic effect found on the cultured rat cortical neurons of the complex of the ovine prion protein (OvPrP(C)) and RNA. 19,20 Besides, unique quadruplex structure and selective interaction of an RNA aptamer against bovine prion protein and may inhibits the prion disease propagation.…”
Section: Introductionmentioning
confidence: 99%
“…This refolding parallels the relative ease of producing PrP-res forms, but not infectivity, in a test-tube. 4,[10][11][12] Dilution of the chemical denaturants here did not restore infectivity. While restoration of TSE agent infectivity has been tried for many years in various preparations, 39,55 a small amount of infectivity was recently restored by combining phenol purified 263K brain nucleic acids with recombinant PrP.…”
Section: Discussionmentioning
confidence: 65%
“…Misfolded recombinant PrP is not reproducibly infectious in animal or culture assays, even though massive amounts of PrPres amyloid are readily generated in a test tube. 4,[10][11][12][13] Huge increases in PrP-res can also coincide with a >5 log loss of FU-CJD agent from chronically infected living cell cultures. 12 This PrP-res is indistinguishable from the "infectious" PrP-res form, yet it is unable to produce any detectable agent in sensitive infectivity culture assays.…”
Section: Introductionmentioning
confidence: 99%